UNJUK KERJA MOTOR INDUKSI ROTOR LILIT SEBAGAI VARIABEL-TRANSFORMATOR (The Performance of a Wound Rotor Induction Motor used as a Variable Transformer) - Lukman Subekti; Ma'un Budiyanto (Jurusan Teknik Informatika, 2009)
Generally induction motor is used as a tool to change electric power to mechanic one. In forced condition wound-rotor induction motor can be used as transformer. This case can be accepted for both machines work by induction principle. Stator is the primary side of a three phase-transformer. Magnetic field produced by stator cuts across rotor conduction. This induction voltage cases the rotor current to flow. However, induction motor is one of non-linear load and be able to cause harmonic in alternating current.The objective of this research is to acknowledge the work of wound-rotor induction motor when its function is changed into a transformer.The research was done by the wound rotor supplied sinusoidal voltage as the primary of a three phasetransformer. The magnetic filed produced by rotor cuts across stator conductor. Rotor position was regulated from 0o, 45o, 90o, 135o, up to 360o. In stator winding, the amount of emf induced proportional to the rate of flux change and the number of its wound.The result of research shows that wound-rotor induction motor can be used as variable transformer. Voltage change obtained is about 8%. Voltage waved) form is defect sinusoidal. The average value of Total Harmonic Distortion (THD) is 1.8% for displacement of rotor angle from 0o up to 360o.